Comparative Analysis Of The Origin And Adaptation Of Original Words In English And Uzbekistan - O'ktamova, Mokhigul; Ravshanova, Jayrona (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
This article provides a comparative analysis of the origin, morphological and phonetic adaptation, and lexical adoption of loanwords in English and Uzbek. The study studies not only words that entered the Uzbek language from English, but also words that were borrowed from other languages ​​in English. The article compares the pronunciation, spelling, role in syntax, and semantic changes of loanwords. This identifies linguistic processes between the two languages, lexical changes, and the development of the language in a cultural context. The results of the study may be useful in understanding loanwords and studying language development.